Penerapan Terapi Rendam Kaki Air Hangat dalam Menurunkan Tekanan Darah pada Pasien Hipertensi - A.Theresia; MK. Fitriani Fruitasari; V. Yosefpa Windahandayani (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Hypertension is a global health issue and major risk factor for cardiovascular disease, requiring lifelong medication. In addition to pharmacological treatment, healthy lifestyle changes and non pharmacological therapies such as warm water foot soaks, can help prevent complications by inducing vasodilation to lower blood pressure. This study aims to describe nursing care for hypertensive patients, focusing on the application of warm water foot soaks to reduce blood pressure in an inpatient setting. Methods a descriptive case study approach was used three hypertensive respondents. The intervention involved 15 minute warm water foot soaks at a temperature of 39-40°C, conducted once daily for three days. Data were collected using digital sphygmomanometers and observation sheets, with measurements taken before and after the intervention. Results, after the therapy, all respondents showed an average reduction in blood pressure, with systolic pressure decreasing by 6,6 mmHg and diastolic by 2,3 mmHg. Respondents also reported felling more relaxed and experiencing lighter sensations in their legs. Conclusion, warm water foot soak therapy is an effective, safe, and cost efficient non pharmacological intervention for hypertensive nursing care, suitable for implementation by both nurses dan families.